Recursos gen?ticos vegetais e o estado da arte do ensino dos RGVs no Brasil - Santos J?nior, S?rgio R?mulo Alves (2023)
Studies started in 2007 with collection expeditions to rescue germplasm in Bahia gave rise to the Stylosanthes Germplasm Bank at the State University of Feira de Santana. This work aimed to evaluate the current situation of the Stylosanthes Germplasm Bank of the State University of Feira de Santana and its perspectives of use and sought to approach how the teaching of Plant Genetic Resources is taking place in undergraduate and graduate programs. related to the major areas of Biological Sciences and Agricultural Sciences according to CAPES classification. Through the search carried out in the accesses deposited in the bank and the passport data of the same. Where there was a change in the nomenclature that was outdated and noted in Excel spreadsheets, later reinserted in the BAG. The (Stylosanthes Germplasm Bank -UEFS) has an approximate number of 570 accessions from expeditions from 2007 to 2019, with greater representation for the Central North Baiano mesoregion. In this way, the maintenance of Stylosanthes spp. it is of great value for the semi-arid region and contributes directly to the promotion of future research and training of human resources specialized in the management of these RGVs. The same being the starting point for research to determine the state of the art of teaching RGVs in the regions of Brazil, where an exploratory-descriptive study with a qualitative and quantitative approach was carried out, starting with the survey of educational institutions that offered courses in the major areas of agricultural and biological sciences. Data referring to recognized courses were collected from the Coordination for the Improvement of Higher Education Personnel (Capes) database, adopting as a basis the Undergraduate, master?s and Doctorate courses that belonged to the respective areas (Agrarian Sciences I and Biological Sciences). Associated with research at CAPES, searches were also carried out in indexed journals. They were analyzed regarding the offer of the Vegetal Genetic Resources curricular component in the menus and in the curriculum of courses in the major areas of Agricultural and Biological Sciences in public Universities, whether state or federal, in all regions of the Brazilian territory. When analyzing the relationship with the area of Plant Genetic Resources, it was observed that there are 642 courses that adhere to the teaching of RGVs in their respective curricula, being at graduation: 199 courses for the major area of Biological Sciences and 275 courses for the major area of Agricultural Sciences. For Graduate programs, the data are: 87 courses for Biological Sciences and 81 courses for Agricultural Sciences. In short, the BGF-UEFS, acts until the present moment as a watershed in the conservation and maintenance of the genus Stylosanthes spp., allowing research to be carried out and specialized human resources to be formedthrough the most varied levels, promoting other research regarding to the current state of teaching RGVs in Brazil and its correlation with the regions that form it.